VALUES OF STRUGGLE IN THE NOVEL SISI TERGELAP SURGA BY BRIAN KHRISNA - Setiawan, Jodi Ari (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
This study was conducted to describe the values of struggle contained in Brian Khrisna's novel Sisi Tergelap Surga (The Darkest Side of Heaven). The research method used in this study is a qualitative descriptive method. The data in this study consists of quotations in the form of words, phrases, or sentences that contain values of struggle. The source of data for this study is the novel Sisi Tergelap Surga by Brian Khrisna. The data collection techniques used are reading and note-taking techniques. The data validity technique used in this study is theoretical triangulation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of this study on the novel Sisi Tergelap Surga reveal the value of self-sacrifice, as demonstrated by the characters Gofar, Sobirin, Juleha, and Rini. The value of mutual respect is shown by the characters Danang, Esih, Tomi, and Juleha. The value of unity is demonstrated by the characters Pulung, Karyo, the silver-painted boy, Kuncahyo, and the frame maker. The value of cooperation is shown by the characters Tomi, the three teenagers, Danang, and Mr. Syamsuar.